Cohort profile: the Taicang and Wuqiang mother–child cohort study (TAWS) in China. Issue 5 (25th May 2022) - Wang, Jie; Duan, Yifan; Yang, Jiaxi; Li, Jun; Li, Fang; Zhou, Pinjiao; Liu, Changqing; Zhao, Yongli; Gu, Xuyang; Yuan, Changzheng; Yin, Shian; Yang, Zhenyu; et al.
Abstract : Purpose: The Taicang and Wuqiang cohort study (TAWS) was established to examine the association between early-life nutrition and children's health, and to explore the potential roles of maternal health, metabolites and microbiota in children's health in two different regions of China. Participants: A total of 7041 mother–child pairs were recruited during early pregnancy (n=4035, 57.3%) or delivery phase (n=3006, 42.7%) from health centres or hospitals in Taicang and Wuqiang. Mother–child pairs were followed up three times during pregnancy, once during delivery, and 7–10 times in the 3 years after delivery. Questionnaires were used to collect data on diet, supplementary intake, physical activity, depression scale, disease occurrence, feeding practice and development quotient of children. Anthropometric measurements of mothers and their children were assessed at each visit. Pregnancy outcomes were extracted from medical records. Biospecimens were collected and stored, including venous blood, cord blood, urine, stool, breast milk, cord and placenta. Findings to date: Data from the TAWS cohort showed different baseline characteristics of participants at the two sites of TAWS. Abnormal metabolism occurred among newborns whose mothers were diagnosed with gestational diabetes mellitus. Maternal serum folic acid above 14.5 ng/mL at early pregnancy was associated with a reduced risk of delivering small-for-gestational-age newborns. Future plans: The association between maternal nutrition and the health of offspring will be examined at various follow-up visits. Biomarkers will be analysed to assess the associations between early-life nutrition and child development, immunity and health. Strategic recommendations for optimal infant feeding practices, obesity prevention and routine healthcare items will be developed and proposed based on the findings from the study. Children in this prospective cohort study will be followed up once a year until age 12 years to further examine the relationships between early-life nutrition and children's long-term development and health.